PENERAPAN PEMBELAJARAN AKTIF (ACTIVE LEARNING) DENGAN METODE MIND MAP UNTUK MENINGKATKAN KREATIVITAS BELAJAR BIOLOGI SISWA KELAS XI A3 SMA NEGERI 1 NGEMPLAK BOYOLALI - Maret Tanti, Puput Dwi; Santosa, Slamet; Sajidan, Sajidan (Pendidikan Biologi, 2011)
ABSTRACT ? This research  aims at improving the creativity of learning biological science through active learning by using mind-map method towards eleventh grade students of science 3 program (XI A3) at SMA Negeri 1 Ngemplak, Boyolali. This research is a Classroom Action Research which was conducted in two cycles. Each cycle consists of four stages: planning, action, observation, and reflection. The subject of this research is the eleventh grade students of science 3 program (XI A3) at SMA Negeri 1 Ngemplak, Boyolali in 2010/2011 academic year. The data of this research were collected through observations, questionnaires, and interviews. The technique of data analysis uses descriptive analysis technique and the data validity was obtained by using the technique of triangulation method. The result of this research shows that the Classroom Action Research which was done through active learning by using mind-map method can give improvement towards the creativity of learning biological science towards the eleventh grade students of science 3 program (XI A3) at SMA Negeri 1 Ngemplak, Boyolali. It can be seen from the result of observations, questionnaires distribution, and interviews. The overall mean of percentage achievement score for each indicator based on the observation of students? creativity in the first cycle is about 76% and about 84.67% in the second cycle (with 8.67% increase). Meanwhile, the overall mean of percentage achievement score for each indicator based on questionnaires of students? creativity in the first cycle is about 77.43% and about 78.87% in the second cycle (with 1.44% increase). Based on the result, it can be concluded that the implementation of active learning by using mind-map method can improve the creativity of learning biological science towards the eleventh grade students of science 3 program (XI A3) at SMA Negeri 1 Ngemplak, Boyolali. Keyword: Active Learning, Mind Map, and Learning Creativity.